Understanding the Effects of Mental Health on Reproductive Health Service Use: A Mixed Methods Approach. Issue 1 (2nd January 2016) - Bell, Sue Anne; Lori, Jody; Redman, Richard; Seng, Julia
Abstract : Appropriate and woman-led health care for displaced women is essential to respecting basic human rights. In this article, we describe the results of an analysis of the association between mental health and reproductive health service use from a sample of Congolese refugee women residing in short- and long-term camps in Rwanda, with a post-hoc qualitative potion added to expand upon the data-based results. Our findings suggest that structural factors including health policy initiatives affect or even inhibit individual care choices.